EXPLORING EFL STUDENTS' PERCEPTIONS OF THE USE OF PODCAST/TED TALK IN EXTENSIVE LISTENING CLASS - Muhammad Handi Gunawan; Indra Cipta Putra Mandiri; Didi Suherdi; Eisha Sabila Dieni Hanifa; Aninda Putri Gunawan (University of Kuningan, 2023)
Podcasts and TED Talks are currently the most widely used resources to facilitate extensive listening activities. Students can benefit greatly from the scaffolding provided by podcasts/TED Talks as they practise extensive listening. In light of the demographics of Indonesian EFL students, this article aims to perform a qualitative analysis of EFL students' perceptions on the usage of podcasts/TED Talks as resources for their extensive listening activities. The primary information of the analysis comes from a post-course reflection questionnaire that was given out. The experiences that the students had during the course are the main focus of this reflective questionnaire. Five of the 23 students were picked for an interview to further discuss their questionnaire responses. The findings of the study revealed that students have largely positive views of using podcasts/TED Talks inside and outside the classroom. The students perceived that listening to podcasts/TED Talks gives them freedom of choosing the topics, flexibility in strengthening their listening skills, and motivation to learn more about listening.Keywords: extensive listening; podcast; TED Talks